The Effect of Financial and Non-Financial Incentives on Employee Performance and Organizational Productivity of Nepalese Commercial Banks - Karki, Shreya (Nepalese Journal of Business, 2024)
The study examines the effect of financial and nonfinancial incentives on employee performance and organizational productivity in the context of Nepalese commercial banks. Employee performance and organizational productivity are selected as the dependent variables. The selected independent variables are salary, bonus, recognition, job promotion, training and development. The study is based on primary data with 145 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and impact of financial and nonfinancial incentives on employee performance and organizational productivity in the context of Nepalese commercial banks. The study showed that salary has a positive impact on employee performance and organizational productivity. It implies that increase in salary leads to increase in level of employee performance and organizational productivity. Moreover, bonus has a positive impact on employee performance and organizational productivity. It means that increase in bonus leads to increase in employee performance and organizational productivity. Likewise, training and development have a positive impact on employee performance and organizational productivity indicating that increase in training and development opportunities lead to increase in employee performance and organizational productivity. Furthermore, recognition has a positive impact on employee performance and organizational productivity. It implies that recognition in the organization leads to increase in employee performance and organizational productivity. Likewise, job promotion has a positive impact on employee performance and organizational productivity indicating that efficient and timely promotion leads to increase in level of employee performance and organizational productivity.